Novel Synthesis Methodology for Controlling Zero-Current Zero-Voltage Transition DC/DC Boost Converter - Thejel, R.H.; Ali, Ramzy S.; Majeed, Elaf J. (Basrah Journal for Engineering Sciences, 2006)
Among the soft-switching techniques, the Zero-Current Zero-Voltage Transition (ZCZVT) technique is used in this paper. It is based on the Resonant Transition Mechanism requirements, which permit newcomers to perceive the Resonant Transition techniques as a whole instead of dissimilar soft-switching techniques. The open loop operation of the power circuit (DC/DC Boost Converter) and control circuit have been implemented and tested with MatLab software. The simulation test facility and the analytical development tools being used are described. The derivation of closed loop control strategy based on fuzzy logic control with nonlinear fuzzy sets for input and output variables is described in detail. The closed loop simulation results that describe the performance of the proposed converter with this control strategy due to different effects are also included.